Development of HOTs-Based Formative Numeration Assessment Instruments on Fractions Material for Grade Junior High School - Finu, Maria Dafrosa; Bhoke, Wilibaldus; Tali Wangge, Maria Carmelita; Bela, Maria Editha (Desimal: Jurnal Matematika, 2026)
Strengthening students’ numeracy competence and higher-order thinking skills has become an important priority in contemporary mathematics education, particularly within curriculum reforms that emphasize analytical reasoning and meaningful problem solving. However, assessment practices in many mathematics classrooms still focus primarily on procedural knowledge and lower-order cognitive processes, limiting opportunities for students to demonstrate deeper mathematical understanding. This situation highlights the need for assessment instruments that integrate numeracy development with higher-order thinking skills (HOTS) in authentic learning contexts. This study aims to develop a HOTS-based formative numeracy assessment instrument for seventh-grade students on the topic of fractions and to evaluate the feasibility of the developed instrument for classroom use. The research employed a research and development approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study involved 64 students from classes VII A and VII B at SMP Negeri 2 Bajawa. Data were collected through interviews, classroom observations, expert validation sheets completed by mathematics teachers, and student response questionnaires. The findings indicate that the developed instrument meets the criteria of validity and practicality for mathematics learning, with expert validation reaching 82.85 percent, teacher responses 87.77 percent, and student responses 84.92 percent. The assessment tasks encourage contextual problem solving and analytical reasoning related to fraction concepts.